Exploring Gender Disparities in Science Achievement : The Impact of Student Engagement among Secondary School Students in West Bengal - Pal, Raj Kumar; Dey, Antara (JOURNAL OF INDIAN EDUCATION, 2024)
This research is a cross-sectional survey that investigates the influence of student engagement on science achievement. Multistage sampling procedures were used to determine the sample of secondary school students (n = 1232). The responses from the respondents were gathered using the student engagement in learning scale and end-of-year examination marks in physical science subject were considered as science achievement. Confirmatory factor analysis and moderation analysis were utilised for data analysis. The findings indicate that there is a significant relationship between student engagement and science achievement. The results show that emotional sub-scale is a better predictor of science achievement (β = 0.23, p<0.05), than behavioural sub-scale (β = 0.32, p<0.05), and cognitive sub-scale (β = 0.38, p<0.05). Thus, this study suggests that school administrators and instructors need to plan and implement interesting activities to increase student engagement.